(untitled) (The Strategic Review for Southern Africa, 2020)
This book consists of six chapters. The first chapter deals with the essence of “Memory from the Margins”. The second chapter discussed the ‘Ethiopian revolution and the Dergue Regime’s red terror (1974-1978)”. The third and fourth chapters also discuss post-Dergue “Transitional influences (1991-2005)” and “the shape of memory (2003-2010)”. The fifth chapter covers the “Tour as traumatic performance, 2010 to present)” and the last chapter concludes “on the memory and future transitions”. First, I would like to appreciate the author for presenting us her book about one of the key chapters in modern Ethiopian political history: the history of Red Terror and its legacy on memory, history and quest for democracy, torture, trauma, survivor docent/victims, reconciliation, museum and transitional justice as well as the ideals “reform and revolution”. This book is timely and detailed in terms of discovering the Red Terror atrocities and survivors’ trauma and capturing similar experiences in other parts of the world.